VARIASI PENAMBAHAN SIKACIM PADA BETON POROUS - Gusneli Yanti; Zainuri; Shanti Wahyuni Megasari (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Pervious concrete is environmentally friendly concrete because it has interconnected cavities that produce a permeable material, allowing it to drain water quickly and reduce runoff so that it is possible to drain water quickly and reduce runoff. This concrete can be applied to parking areas, sidewalks for pedestrians, and others. The purpose of this study was to determine the characteristics of the concrete by observing its compressive strength and porosity. The method used is the experiment with a sample of cylindrical specimens measuring 150 x 300 mm. This study uses coarse aggregate, cement, water, and the percentage variation of the addition of SikaCim Concrete Additive admixture by 0% (control); 0.3%; 0.5%; 0.7% by weight of cement. The water-cement ratio used was 0.25 and 0.30 and the ratio of cement and coarse aggregate was 1:3 and 1:5. The results showed that the compressive strength value of pervious concrete increased along with the smaller the value of the cement and coarse aggregate ratio. The pervious concrete with a water-cement ratio of 0.25 is higher than that of 0.30. There is a relationship between porosity and compressive strength. Compressive strength generally increases with decreasing porosity. The highest average value of compressive strength with variations in the addition of SikaCim of 0.5% and a ratio cement and coarse aggregate of 1:3 and a water-cement ratio of 0.3, with an average compressive strength value of 18.08 MPa, and included in category B which is used for parking areas.